Addition Of Gibberellin (GA3) to Gladiolus Cormel Growth (Gladiolus communis L.) on Various Medium in Vitro - Egy Aerani; Rina Srilestari; Ari Wijayani (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2017)
Gladiolus flower can be multiplied by using corm or cormel. The multiplication of this flower using plating material takes a long time, about 3,5-6 months. By using in vitro method, the seed of this flower can be produce in relatively short time. The aim of this research was to determine the interaction of gibberellins on any kind of media (MS, B5, and MS + vitamin B5), to determine the perfect combination of concentration of Gibberelin, and to determine the perfect type of media that can be use for induction of root and shoot of gladiolus cormel. The research design used was a Completely Randomized Design (CRD) of the factorial pattern with 3 replications. The first factors (concentration of Gibberellin) G1: 1 ppm, G2: 2 ppm, dan G3: 3 ppm, the second factors (type of media) M1: MS , M2: B5 (Gamborg) , M3: MS + B5 vitamin. The result showed that the addition of various concentration of Gibberelin (GA3) and any type of media had no significantly improve the growth of gladiol cormel explant, by addition concentration of Gibberelin 2 ppm has significantly improved fresh weight of planlet and percentage of life, by addition B5 media, has significantly improved length of root and growth of shoot, and by using MS media with B5 vitamin has significantly improved the growth of shoot, height and fresh weight of planlet.Keywords: Gladiol, gibberellin, plant media, in vitro